Employment status changes of workers after referral to an occupational disease clinic. Issue 6 (27th November 2018) - Beyan, Ayse Coskun; Demiral, Yucel; Cimrin, Arif
Abstract : Objective: Occupational diseases (OD) are among the most significant issues of work life, with economic, medical, social, and ethical aspects. The majority of studies concerning OD focus on the causes or medical outcomes of OD. There are a limited number of studies investigating the social and economic impacts of being diagnosed with an OD. One of the important social aspects of OD is the employability of workers after an OD diagnosis. The aim of this study is to evaluate the changes in employment status after the OD diagnosis process. Methods: This is a cross sectional study. There were 204 eligible cases, and 198 (97%) completed the study. The study data were obtained from patient files, including OD Committee reports and questionnaires applied via telephone interview. Results: Among the 198 applicants, 170 (85.9%) were male and 146 (73.7%) were diagnosed with an OD. Of these workers, 106 (53.5%) had quit their current jobs. Of those workers, 89 out of 106 were in the OD group, and 17 were in the non‐ OD group. Diagnosis with OD (OR: 3.1 CI: 1.4‐6.8) and non‐union membership (OR : 11.1 CI : 5.2‐23.5) increased the likelihood of quitting the job after an OD diagnosis. Conclusion: The short‐term prognosis of OD was relatively poor. OD diagnosis or even referral to an outpatient clinic may cause quitting the job. Policies should account for the risk of unemployment after an OD diagnosis, and OD surveillance systems should obtain data on the employment status of workers following diagnosis.